VD_FINDINFO Jug / 2013 / 169 vom 7. Oktober 2013 - VD Tribunal cantonal (2013)
COURTAGE, SOCIÉTÉ SIMPLE, SALAIRE, RÉSILIATION | 156 CO, 412 al. 1 CO, 412 al. 2 CO, 412 CO, 413 al. 1 CO, 413 CO, 530 al. 1 CO, 530 CO